INSTRUMEN RATIFIKASI PERJANJIAN PERDAGANGAN INTERNASIONAL: REZIM PUTUSAN MAHKAMAH KONSTITUSI NOMOR 13/PUU-XVI/2018 - Prita Amalia; Garry Gumelar Pratama; Wahyu Agung Laksono; Anindya Saraswati Ardiwinata (Veritas et Justitia, 2023)
The intrusive character inherent in international trade agreements makes the particular form of the treaty unique compared to other treaties. The trade agreements' intrusiveness means the treaty impacts individual rights relatively more than other treaties on its implementation. Confirming such a particular character, the Indonesian Constitutional Court, via its Decision No. 13/PUU-XVI/2018, provides additional criteria for the treaty ratified through an act, in addition to the general forms of treaties. This study comprehensively discusses the consistency of the instrument form and the clarity of the reference regulations related to the procedure for ratifying the international trade agreement in Indonesia after the ruling of the 2018 Constitutional Court Decision. This study uses a normative juridical approach by making a library of data covering principles, laws, and regulations or legal theories relevant to research as the main material. The study shows that Constitutional Court Decision No. 13/PUU-XVI/2018 has allowed the international trade agreement to be ratified consistently using a legislative act replacing the past practice of using a presidential act. Moreover, the provisions on international trade agreements ratification under Indonesian trade law and Indonesian treaty law must be enforced using "lex specialis derogat lex generalis" principle. Although they share the same norms after the Constitutional Court's Decision 13/2018, specific provisions under the trade law prevail over the general provisions of the Indonesian treaty law.